2016
DOI: 10.1097/mbc.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein and mean platelet volume as predictive values after percutaneous coronary intervention for long-term clinical outcomes

Abstract: This study was designed to establish the relationship of high-sensitivity C-reactive protein (hsCRP) and mean platelet volume (MPV) with the development of adverse outcomes after percutaneous coronary intervention (PCI). hsCRP levels and MPV were analysed in 372 patients who underwent PCI, with the primary endpoint as major adverse cardiac and cerebrovascular events (MACCE): a composite of cardiac death, myocardial infarction (MI), target vessel revascularization (TVR), ischemic stroke and stent thrombosis. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
3
15
0
1
Order By: Relevance
“…Comorbid factors, LVEF, medical treatment approaches, results, and complications of interventional treatments can affect treatment results and MACE regardless of the level of inflammation. Similarly to our study, due to the abovementioned adverse factors, in previous studies examining the relationship between inflammation parameters and MACE, the specificity rates are generally lower than the sensitivity rates [ 32 , 33 ]. In risky clinical situations such as STEMI, markers that do not require additional costs, such as WMR, have a high sensitivity in determining risk and may be more valuable in clinical risk classification and treatment planning.…”
Section: Discussionsupporting
confidence: 75%
“…Comorbid factors, LVEF, medical treatment approaches, results, and complications of interventional treatments can affect treatment results and MACE regardless of the level of inflammation. Similarly to our study, due to the abovementioned adverse factors, in previous studies examining the relationship between inflammation parameters and MACE, the specificity rates are generally lower than the sensitivity rates [ 32 , 33 ]. In risky clinical situations such as STEMI, markers that do not require additional costs, such as WMR, have a high sensitivity in determining risk and may be more valuable in clinical risk classification and treatment planning.…”
Section: Discussionsupporting
confidence: 75%
“…Elevated MPV along with increased inflammation biomarkers (e.g., C-reactive [CRP], interleukin-6 [IL-6] among other) were reported in many conditions which are characterized by low-grade inflammation including ischemic stroke [ 49 ], utricaria [ 50 ], postoperative atrial fibrillation [ 51 ], adverse outcomes following percutaneous coronary intervention [ 52 ], myocardial infarction [ 53 ], urinary tract infection [ 54 ], exacerbations of COPD [ 55 ], hypertension [ 56 ], rheumatoid arthritis (RA) [ 57 ], osteoarthritis [ 58 ], and pneumonia [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 addition, it can also be used for the prediction of future development of atherosclerotic diseases including stroke and cardiovascular disease. [23][24][25] But wide variation in the results between this study and other studies could also be due to different definitions of END, time scale of assessment of acute stroke and varied process of selection of patients.…”
Section: Discussionmentioning
confidence: 57%
“…23 Moon AR et al, found the association of hs (high sensitivity) CRP and Mean Platlet Volume (MPV) as one of the predictors of long term clinical outcomes in post Percutaneous Transluminal Coronory Angioplasty (PTCA) patients. 24 Jimenez MC et al, also found significant association between hs CRP and stroke severity in hypertensive patients. 25 addition, it can also be used for the prediction of future development of atherosclerotic diseases including stroke and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 90%